Outcome and Complications of Frontal Sinus Stenting: A Case Presentation and Literature Review - Khan, Mohammed A.; Alshareef, Waleed A.; Marglani, Osama A.; Herzallah, Islam R. (Case Reports in Otolaryngology, 2020)
Introduction. Frontal sinus surgery remains challenging to manage because of its complex anatomy and narrow outflow tract. A number of studies suggest the success of frontal sinus stenting to reduce postoperative complications in endoscopic frontal sinus surgery. However, failure and complications of frontal sinus stenting may occur. Method. We present a case of frontal sinus stenting with migration of the stent and erosion of the lamina papyracea together with a granulomatous reaction around the stent. PubMed and Medline search was also conducted to study the current evidence on frontal sinus stenting benefits and complications. Results. Still there are no guidelines or universally accepted indications for the use of frontal sinus stenting in the literature. A limited number of studies suggest the success of frontal sinus stenting to reduce postoperative stenosis in endoscopic frontal sinus surgery. However, failure and complications of frontal sinus stenting may occur. Infection, pain, edema, and stent obstruction may also occur. Our case report also highlights the potential of orbital complications as well as the consequences of inducing a granulomatous reaction. Conclusion. The value of frontal sinus stenting is still a subject of debate. Complications of frontal sinus stenting are not uncommon and thus necessitate regular follow-up.